2015
DOI: 10.1111/dme.12996
|View full text |Cite
|
Sign up to set email alerts
|

Performance of three glomerular filtration rate estimation equations in a population of sub‐Saharan Africans with Type 2 diabetes

Abstract: The MDRD equation seems to have a modest advantage over CKD-EPI and CG in estimating GFR and detecting impaired renal function in sub-Saharan African patients with Type 2 diabetes. The overall relatively modest correlation with CrCl, however, suggests the need for context-specific estimators of GFR or context adaptation of existing estimators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“… 46 N/L ratio, which combines the predictive power of both increased neutrophil count and decreased lymphocyte count, 47 was associated with reduced eGFR in our study, as also found in other studies. 23 48 49 Indeed previous studies, which included patients with CKD on haemodialysis 23 48 and predialysis, 49 showed that an increased N/L ratio was associated with known inflammatory markers such as tumour necrosis factor-α, 23 interleukin 6 and hsCRP levels. 49 These studies demonstrated that these well-established markers of inflammation were independent factors for predicting N/L ratio, thus presenting N/L ratio as an inflammatory biomarker for patients with CKD.…”
Section: Discussionmentioning
confidence: 96%
“… 46 N/L ratio, which combines the predictive power of both increased neutrophil count and decreased lymphocyte count, 47 was associated with reduced eGFR in our study, as also found in other studies. 23 48 49 Indeed previous studies, which included patients with CKD on haemodialysis 23 48 and predialysis, 49 showed that an increased N/L ratio was associated with known inflammatory markers such as tumour necrosis factor-α, 23 interleukin 6 and hsCRP levels. 49 These studies demonstrated that these well-established markers of inflammation were independent factors for predicting N/L ratio, thus presenting N/L ratio as an inflammatory biomarker for patients with CKD.…”
Section: Discussionmentioning
confidence: 96%
“…Given that results from studies evaluating the performance of estimated GFR (eGFR) equations in black Africans have been inconsistent ( 20 , 21 ), we calculated race and gender-specific eGFR using the Modification of Diet in Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations. A recent evaluation of eGFR equations among Africans with T2D showed that the MDRD was associated with lower bias compared to the CKD-EPI and Cockcroft–Gault equations ( 22 ). Thus, we used eGFR calculated from the MDRD equation for our multivariate analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the relative superiority of MDRD to the CG formula for detecting various stages of AKI early after kidney donation, other researchers have shown the advantage of MDRD over both the CG formula and the Chronic Kidney Disease Epidemiology Collaboration equation for estimating GFR and diagnosing impaired renal function. 11 Owing to the nonlinear relation between creatinine/cystatin C and GFR, 4 relatively small initial incremental increases in these markers correlate with significant decreases in GFR. This nonlinearity is more pronounced when using kinetic GFR as a measure, as reflected by the greater percentile reduction in kinetic GFR compared with CG and MDRD GFR formulas on day 1 after donation ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%